The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.7554/elife.78944
|View full text |Cite
|
Sign up to set email alerts
|

Transcription elongation is finely tuned by dozens of regulatory factors

Abstract: Understanding the complex network that regulates transcription elongation requires the quantitative analysis of RNA polymerase II (Pol II) activity in a wide variety of regulatory environments. We performed native elongating transcript sequencing (NET-seq) in 41 strains of S. cerevisiae lacking known elongation regulators, including RNA processing factors, transcription elongation factors, chromatin modifiers, and remodelers. We found that the opposing effects of these factors balance transcription elongation … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
29
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(36 citation statements)
references
References 140 publications
(215 reference statements)
7
29
0
Order By: Relevance
“…29 Steady-state RNA-seq data and RNAPII profiling through NET-seq showed that paf1Δ cells exhibit widespread transcriptional misregulation of coding genes and upregulation of antisense transcripts, particularly for Set2 Repressible Antisense Transcripts (SRATs). [30][31][32] This is consistent with the loss of Set2-dependent H3 K36me3 in paf1∆, and also ctr9∆, mutants. 11,[30][31][32] While it is apparent that Paf1C broadly impacts gene expression and chromatin states, technological limitations have confounded interpretations of its functions.…”
Section: Introductionsupporting
confidence: 83%
See 3 more Smart Citations
“…29 Steady-state RNA-seq data and RNAPII profiling through NET-seq showed that paf1Δ cells exhibit widespread transcriptional misregulation of coding genes and upregulation of antisense transcripts, particularly for Set2 Repressible Antisense Transcripts (SRATs). [30][31][32] This is consistent with the loss of Set2-dependent H3 K36me3 in paf1∆, and also ctr9∆, mutants. 11,[30][31][32] While it is apparent that Paf1C broadly impacts gene expression and chromatin states, technological limitations have confounded interpretations of its functions.…”
Section: Introductionsupporting
confidence: 83%
“…[30][31][32] This is consistent with the loss of Set2-dependent H3 K36me3 in paf1∆, and also ctr9∆, mutants. 11,[30][31][32] While it is apparent that Paf1C broadly impacts gene expression and chromatin states, technological limitations have confounded interpretations of its functions. Many previous studies have relied on stable null alleles, which allow cumulative effects to accrue.…”
Section: Introductionsupporting
confidence: 83%
See 2 more Smart Citations
“…Finally, in at least some cases, it is clear that elongation rates are not only indirectly influenced by structural features of DNA, RNA, or chromatin, but are actively regulated in response to various cellular stimuli, with dysregulation of elongation rates potentially contributing to disease progression [14].Other studies have focused specifically on pausing of Pol II. Aside from the pronounced pausing that occurs proximal to the promoter, many, typically more subtle, pause sites occur within gene bodies, and, in the aggregate, these sites have a major effect on the dynamics of transcription elongation [16][17][18][19] (see also [20] for a recent study in yeast). These gene-body pause sites replicate well across experiments but vary substantially in their density across genes; they also occur in divergent antisense transcripts and enhancer RNAs as well as in gene bodies [18].…”
mentioning
confidence: 99%